Analisis Optimalisasi Kinerja UMKM Melalui Perencanaan Inovasi - Atmojo, Cahyo Tri; Wahono, Heru Totok Tri (Universitas Negeri Semarang, 2023)
This article aims to provide an in-depth understanding of the importance of designing innovations in optimizing performance at UD Jenang Kelapa Muda. By analyzing the factors that influence the implementation of innovations and exploring case studies of MSMEs that have successfully implemented innovations, this article is expected to provide valuable insights for UD Jenang Kelapa Muda owners, researchers, and the government in advancing this sector. The method used in this study uses qualitative descriptive method. The research data collection methods are surveys, interviews, and data analysis. The survey conducted showed that there is a high demand for young coconut jenang at UD Jenang Kelapa Muda with new flavors. This provides an opportunity for UD Jenang Kelapa Muda to reach a wider market segment and increase revenue.